KAUM muda dan budaya maritim Nusantara / Ni Kadek Sri Jayanti...[et al] ; editor, M. Alie Humaeda, Lukman Solihin - Ni Kadek Sri Jayanti; Alie Humaeda, M.; Lukman Solihin (Ifada Press, 2015)
xLiii, 180 hlm. ; 21 cm